Low Infrared Emissivity Coating Based on Graphene Surface-Modified Flaky Aluminum - He, Lihua (Materials (Basel), 2018)
A low infrared emissivity coating was prepared using graphene surface-modified flaky aluminum complex powders (rGO-FAl) as fillers. The flaky aluminum powders were coated with graphene through chemical bonding. Compared with pure flaky aluminum, the Vis-NIR diffuse reflectance of rGO-FAl complex powders was significantly decreased, which was beneficial to the low glossiness of the coating. After the modification, the glossiness at 60° of the coating with 40% (mass fraction) pigments decreased from 12.8 to 6.7, while the coating maintained low infrared emissivity (0.238~0.247) at a spectral range of 8–14 μm. In the electrochemical impedance spectroscopy (EIS) measurement, at the lowest frequency, the impedance of the Al-rGO test plate was at least two orders of magnitude greater than that of the control Al test plate, and the graphene layer significantly increased the bandwidth of the maximum phase angle, which indicates a good protective effect of the ultra-thin graphene layer on metal in a corrosive environment. The coating with 40% rGO-FAl complex powders can maintain its appearance after 500 h of salt spray corrosion testing. In contrast, the color of the coating with the original aluminum powders changed after only 300 h.